Are Public Sector Workers Underpaid? Appropriate Comparators in a Developing Country - Bales, Sarah (World Bank, Washington, DC, 2014)
How is public sector compensation best aligned with the market? In industrial countries a common reference is the salary paid by private employers for similar jobs (the "jobs approach"). But comparable jobs are formal, and in developing countries the relevant alternative for many public sector workers is informal sector employment. Another approach uses as a reference, the earnings of similar workers in the private sector, regardless of whether their jobs are formal, or informal (the "workers approach"). A potential shortcoming of this approach is that workers may differ in characteristics that are unobservable. The authors assess the importance of this shortcoming, by relying on five econometric methods, four of which correct the bias from unobservable characteristics. The authors focus on state-owned enterprises in Vietnam, which recruited workers on the basis of political loyalty, and other unobservable characteristics. A massive downsizing program, which led to the departure of the most entrepreneurial workers, may have exacerbated the selection bias. However, all the results obtained with the workers approach, fall within a relatively narrow range. They suggest that workers in state-owned enterprises, are overpaid by twenty percent, or more. In contrast, the jobs approach indicates that they could earn two, to six times more in the private sector.